Predictive value of shock index variants on 30-day mortality of trauma patients in helicopter emergency medical services: a nationwide observational retrospective multicenter study - Iirola Timo; Björkman Johannes; Laaksonen Mikael; Nurmi Jouni (Nature Portfolio, 2025)
The original shock index (SI) has been further developed to increase its prognostic value. We aimed to evaluate the predictive value of different SI variants on 30-day mortality among severely injured trauma patients in pre-hospital critical care settings. Adult trauma patients in the national Helicopter Emergency Medical Services (HEMS) registry were evaluated based on the primary outcome of 30-day mortality. SI, SIA (SI multiplied by age), SI/G (SI divided by Glasgow Coma Scale (GCS)), SIA/G (SI multiplied by age and divided by GCS), and SS (SI divided by oxygen saturation) were calculated based on the first vital signs measured at the time of HEMS contact. The area under the receiver operating curve (AUROC) was calculated for each SI variant. In total 4108 patients were included in the study. The overall 30-day mortality was 13.5%. The SIA/G and SI/G had the highest predictive ability (AUROC 0.884 [95% CI 0.869–0.899] and 0.8000 [95% CI 0.7780–0.8239], respectively). The SIA/G yielded good predictive performance between 30-day survivors and non-survivors in the pre-hospital critical care setting.